2016
DOI: 10.1111/eje.12207
|View full text |Cite
|
Sign up to set email alerts
|

A novel anatomical ceramic root canal simulator for endodontic training

Abstract: This novel anatomic root canal simulator is well suited for training undergraduate and postgraduate students in endodontic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 16 publications
(19 reference statements)
1
46
0
2
Order By: Relevance
“…The direct observation of the tooth with an operating microscope helped when the replica had transparent roots. Therefore, as previous authors have described, the evaluators in the present study also found transparency a positive feature for artificial teeth for root canal training, since it helps in the identification of potential procedural errors (Al‐Sudani & Basura , Robberecht et al , Reymus et al ). Nevertheless, brightness and contrast were calibrated and adjusted for every group prior to the study to optimize and homogenize the radiographic appearance of the different teeth.…”
Section: Discussionsupporting
confidence: 81%
“…The direct observation of the tooth with an operating microscope helped when the replica had transparent roots. Therefore, as previous authors have described, the evaluators in the present study also found transparency a positive feature for artificial teeth for root canal training, since it helps in the identification of potential procedural errors (Al‐Sudani & Basura , Robberecht et al , Reymus et al ). Nevertheless, brightness and contrast were calibrated and adjusted for every group prior to the study to optimize and homogenize the radiographic appearance of the different teeth.…”
Section: Discussionsupporting
confidence: 81%
“…A new approach based on 3D printing using a microporous hydroxyapatite‐based matrix (Robberecht et al . ) as printing material seems to be promising for correctly imitating dentine. Not surprisingly, the students assessing the replicas found that their hardness was less comparable to real teeth.…”
Section: Discussionmentioning
confidence: 99%
“…, Robberecht et al . ). Some of the earliest demonstrations utilized CT slices and starch to reconstruct challenging clinical cases such as extracanal invasive resorption (Kim et al .…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 97%
“…Robberecht et al . () developed a porous, radiopaque hydroxyapatite‐based matrix with hardness similar to dentine, to print ceramic models for endodontic lab exercises. Custom designed regenerative endodontic educational models have enhanced preclinical residency exercises (Fig.…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 99%